2016
DOI: 10.1073/pnas.1524875113
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of polyhedra in spherical confinement

Abstract: Dense particle packing in a confining volume remains a rich, largely unexplored problem, despite applications in blood clotting, plasmonics, industrial packaging and transport, colloidal molecule design, and information storage. Here, we report densest found clusters of the Platonic solids in spherical confinement, for up to N = 60 constituent polyhedral particles. We examine the interplay between anisotropic particle shape and isotropic 3D confinement. Densest clusters exhibit a wide variety of symmetry point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 122 publications
2
66
0
Order By: Relevance
“…Such a structure with all positions occupied by one kind of atom closely resembles the densest known packing of 36 identical balls within a spherical container [20,21]. This configuration consists of an outer shell of 32 balls lying tangent to the confining sphere, 20 of those located at the vertices of a distorted regular dodecahedron and the other 12 at the vertices of a dual distorted regular icosahedron.…”
Section: Why Might Tdis Exist In the Melt?mentioning
confidence: 93%
See 2 more Smart Citations
“…Such a structure with all positions occupied by one kind of atom closely resembles the densest known packing of 36 identical balls within a spherical container [20,21]. This configuration consists of an outer shell of 32 balls lying tangent to the confining sphere, 20 of those located at the vertices of a distorted regular dodecahedron and the other 12 at the vertices of a dual distorted regular icosahedron.…”
Section: Why Might Tdis Exist In the Melt?mentioning
confidence: 93%
“…Teich et al found this densest packing configuration via Monte Carlo simulation: they sampled configurations of hard spheres inside a spherical container in the isobaric ensemble while increasing imposed pressure to a putatively high value, thereby compressing the container [20]. They found that in the densest packing formed this way, the inner tetrahedron was not completely sterically immobilized by the outer shell, but instead had some "wiggle room" and vibrated slightly even as the cluster reached its densest possible configuration.…”
Section: Why Might Tdis Exist In the Melt?mentioning
confidence: 99%
See 1 more Smart Citation
“…Such depletion interactions scale with thermal energy (k B T), and thus enable tunable and reversible attractions (14,15). Clever design of shaped or patterned colloids yields "lock-and-key" colloidal interactions (16,17) and so-called "colloidal molecules" (18,19). Grafting ligand-functionalized molecules to colloidal surfaces enables molecular sensing (20,21), and sophisticated design of colloidal self-assembly (22,23).…”
mentioning
confidence: 99%
“…Polyhedra with small asphericity and high rotational symmetry are expected to form such mesophases in between the disordered and crystalline states [17]. Packing small numbers of hard icosahedra in a hard spherical container results in clusters that resemble or match sphere clusters (optimal sphere codes) despite significant faceting of these objects [18].…”
Section: Introductionmentioning
confidence: 99%